2016
DOI: 10.1080/15384101.2016.1148836
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide inhibits prostate cancer by targeting cell cycle regulators, CXCR3 and CXCR7 chemokine receptors

Abstract: Despite state of the art cancer diagnostics and therapies offered in clinic, prostate cancer (PCa) remains the second leading cause of cancer-related deaths. Hence, more robust therapeutic/preventive regimes are required to combat this lethal disease. In the current study, we have tested the efficacy of Andrographolide (AG), a bioactive diterpenoid isolated from Andrographis paniculata, against PCa. This natural agent selectively affects PCa cell viability in a dose and time-dependent manner, without affecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 48 publications
4
20
0
Order By: Relevance
“…CXCR7 might be a therapeutic target for PCa. Mir et al reported that Andrographolide damages PCa cells via targeting the expression of CXCR3 and CXCR7 [ 27 ], supporting the conclusions of the present study. However, the specific molecular mechanisms by which CXCR7 affects PCa remain unclear and further research is needed.…”
Section: Discussionsupporting
confidence: 91%
“…CXCR7 might be a therapeutic target for PCa. Mir et al reported that Andrographolide damages PCa cells via targeting the expression of CXCR3 and CXCR7 [ 27 ], supporting the conclusions of the present study. However, the specific molecular mechanisms by which CXCR7 affects PCa remain unclear and further research is needed.…”
Section: Discussionsupporting
confidence: 91%
“…Another approach to target NF-κB for cancer therapy is the use of cyclooxygenase-2 (COX-2) inhibitors. Andrographolide (Andro), a diterpenoid lactone extracted from Andrographis paniculata, has been reported to be of therapeutic effect in various cancers showing less adverse effects [139].…”
Section: Cyclooxygenase 2 Inhibitorsmentioning
confidence: 99%
“… 18 Previous studies have reported that Andro has a role in PCa inhibition through cell cycle regulation. 19 Andro increases the radiation sensitivity of ovarian cancer cells, enhancing apoptosis and autophagy. 20 In this study, we found that Andro significantly improved the sensitivity of PCa cells to TRAIL-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%